Insight into American tourists experiences with weather in South Africa - Giddy, Julia K.; Fitchett, Jennifer M.; Hoogendoorn, Gijsbert (Bulletin of Geography. Socio-economic Series, 2017)
Weather and climate are often important factors determining the success of a tourism destination and resultant satisfaction among tourists. This is particularly true for South Africa due the predominance of outdoor tourist attractions. Increasing numbers of international tourists have visited South Africa since the fall of apartheid, particularly those from the United States (U.S.), which is an important market for South African tourism. Therefore, this paper seeks to examine a sample of American tourists experience with day-to-day weather and climatic conditions in South Africa. The results show that although respondents did not feel that climatic conditions were an important factor in motivations to visit the country, the day-to-day weather did often impact the enjoyment of their visit. Most notably, weather controlled their ability to participate in outdoor activities. In correlating accounts of unpleasant weather conditions with the meteorological records, a close association emerged, particularly for excessively high temperatures. This indicates that the experiences of American tourists are an accurate indication of climatic unsuitability for tourism, which poses threats to the South African outdoor tourism sector.